Staat, Sicherheit und Gewalt in Kamerun Postkoloniale Perspektiven auf den Dekolonisierungsprozess unter französischer UN-Treuhandverwaltung - Ketzmerick, Maria (Postcolonial Studies, 2019)
The process of state building in Cameroon developed violently despite international observation and the UN mandated fiduciary situation. The central issue was the conflict over the transfer of the monopoly on violence and the communication of security, insecurity and threats, since anti-colonial forces, local elites and international administrators conveyed their claims to the future state through security talks. In thinking together of post-colonial theories and security research, Maria Ketzmerick develops a perspective on the state-building process, which has explanatory content for current conflict situations in Cameroon, and also determines narratives of security that have been updated in the post-colonial state.